THE ROLE AND IMPACT OF ISLAMIC FINANCIAL INSTRUMENTS IN POVERTY REDUCTION IN UZBEKISTAN (International journal of artificial intelligence, 2025)
This scientific paper explores the role and impact of Islamic financial instruments in poverty reduction efforts in the Republic of Uzbekistan. The study is based on the core principles of the Islamic financial system — interest-free financing, risk-sharing, social justice, and equality in ownership. Key instruments such as zakat, sadaqah, qard al-hasan, mudarabah, musharakah, and ijarah are analyzed for their potential in promoting economic and social stability. The research also evaluates the current state of Islamic finance infrastructure and legal frameworks in Uzbekistan, existing practices, challenges, and development prospects. Special attention is given to the opportunities for supporting vulnerable social groups, promoting small businesses, and enhancing financial inclusion through Islamic mechanisms. The paper concludes with practical recommendations for the effective integration of Islamic finance tools in the national poverty alleviation strategy.